Aplikasi Larva Black Soldier Fly (Hermatia illucens) Sebagai Pakan Alami Dan Pakan Buatan (Pelet) Untuk Ikan Rainbow Kurumoi (Melanotaenia parva) [Application Of Black Soldier Fly Larval (Hermetia illucens) As Feed And Artificial Feed (Pellets) For Rainbow Kurumoi Fish (Melanotaenia parva) ] - Abdul Manan; Muhammad Syahrizal Irfan (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Fish flour is raw materials of main protein source for fish feed, however because of its existence day by day gets expensive so that the other alternative feed material needed as the alternate of fish flour that is maggot which is the larva of insects kind of fly which contains crude protein about 42%. This Study was held in Research and Aquaculture Cultivation Center of Ornamental Fish Depok, West Java in January 14th until February 14th 2013. The goal of this Study is to know the aplication of black soldier fly larval (Hermetia illucens) as the feed of rainbow kurumoi fish (Melanotaenia parva). Maggot culture was undertaken by mixing PKM and water with the comparison of 1:2 then fermented in fiber basin. Then interspersed with wire and above it there was a dry banana leaf to lay the eggs and covered by wire again, and then eggs harvesting was undertaken which was moved to the egg hatching basin which contain PKM which had been fermented. After 2 weeks maggot was ready to be harvested from the hatching basin. Maggot and maggot pellets could fulfill the need of nutrition for rainbow kurumoi fish, this case could be seen by the existence of weight increase and length increase of the fish.